The link between empowering leadership and employees' perceptions of the effectiveness of blended working. Issue 3 (2nd February 2022) - Wörtler, Burkhard; Van Yperen, Nico W.; Barelds, Dick P. H.
Abstract : Linked to technological and societal developments, including the COVID‐19 pandemic, employees are increasingly being given the opportunity to blend onsite and remote working including flexibility as to when and where they work. Despite the proliferation of such blended working, there is little empirical research on how leaders in organizations can contribute to facilitating its effectiveness. In the present study, we hypothesized that an empowering leadership style would be positively associated with employees' perceptions of the effectiveness of blended working. Additionally, grounded in Self‐Determination Theory, we hypothesized that the satisfaction of employees' work‐related psychological needs for autonomy and for competence would mediate this relation. Results of a field study ( N  = 405 employees) using a two‐wave panel design supported a cross‐lagged effect of empowering leadership on employees' perceptions of the effectiveness of blended working. However, no evidence was found for the hypothesized mediated relations. Our findings could be of value to organizations as they indicate a specific leadership style that is likely to facilitate the effectiveness of blended working.